… as the length of the vector difference
\[\begin{equation*} \| \vec{u} - \vec{v} \|. \end{equation*} \]
… in the real plane \(\mathbb{R}^2\):
… is
\[\begin{equation*} \| \vec{u} - \vec{v} \| = \left\| \begin{pmatrix} u_1 \\ \vdots \\ u_m \end{pmatrix} - \begin{pmatrix} v_1 \\ \vdots \\ v_m \end{pmatrix} \right\| = \sqrt{{(u_1 - v_1)}^2 + \cdots + {(u_m - v_m)}^2}. \end{equation*} \]
… the closed form as
\[\begin{align*} \| \vec{u} - \vec{v} \| \tag{1} & = \left\| \begin{pmatrix} u_1 \\ \vdots \\ u_m \end{pmatrix} - \begin{pmatrix} v_1 \\ \vdots \\ v_m \end{pmatrix} \right\| \\[1ex] \tag{2} & = \sqrt{(\vec{u} - \vec{v}) \cdot (\vec{u} - \vec{v})} \\[1ex] \tag{3} & = \sqrt{\sum_{i = 1}^{m} (u_i - v_i) (u_i - v_i) } \\[1ex] \tag{4} & = \sqrt{\sum_{i = 1}^{m} {(u_i - v_i)}^2 } \\[1ex] \tag{5} & = \sqrt{{(u_1 - v_1)}^2 + \cdots + {(u_m - v_m)}^2} \end{align*} \]
with
… the closed form as
\[\begin{align*} \| \vec{u} - \vec{v} \| \tag{1} & = \left\| \begin{pmatrix} u_1 \\ \vdots \\ u_m \end{pmatrix} - \begin{pmatrix} v_1 \\ \vdots \\ v_m \end{pmatrix} \right\| \\[1ex] \tag{2} & = \sqrt{(\vec{u} - \vec{v}) \cdot (\vec{u} - \vec{v})} \\[1ex] \tag{3} & = \sqrt{{(\vec{u} - \vec{v})}^\mathsf{T} (\vec{u} - \vec{v})} \\[1ex] \tag{4} & = \sqrt{ \begin{pmatrix} \vphantom{\bigg(} u_1 - v_1 & \cdots & u_m - v_m \end{pmatrix} \begin{pmatrix} u_1 - v_1 \\ \vdots \\ u_m - v_m \end{pmatrix} } \\[1ex] \tag{5} & = \sqrt{(u_1 - v_1) (u_1 - v_1) + \cdots + (u_m - v_m) (u_m - v_m)} \\[1ex] \tag{6} & = \sqrt{{(u_1 - v_1)}^2 + \cdots + {(u_m - v_m)}^2} \end{align*} \]
with
… as shown above, or
\[\begin{equation*} \| \vec{u} - \vec{v} \| = d(\vec{u}, \vec{v}) = \operatorname{dist}(\vec{u}, \vec{v}). \end{equation*} \]
… in Scheme as
my-vector-euclidean-distance
(define (my-vector-euclidean-distance vector other-vector) (my-vector-length (my-vector-subtract vector other-vector)))
in terms of my-vector-length
and my-vector-subtract
.